COVID-safe behaviour before, during and after a youth mass gathering event: a longitudinal cohort study - Tegan Cruwys; Joanne A Rathbone; Mark Stevens; Laura J Ferris (BMJ Open)
Objective As mass gathering events resume in the wake of the COVID-19 pandemic, there is a pressing need to understand (a) engagement in COVID-safe behaviour at these events and (b) how attending a mass gathering impacts subsequent behaviours. This study examined anticipated COVID-safe behaviour before, during, and after a youth mass gathering event.Design Longitudinal cohort study.Setting Self-report data were collected online at five timepoints from secondary-school graduates participating in celebrations linked to an annual week-long youth mass gathering event in Australia.Participants Australian secondary-school graduates completed surveys before the event (N=397), on days 1 (N=183), 3 (N=158) and 5 (N=163) of the event, and 3 weeks after the event (N=140). Of those who completed the first survey, 72 indicated they would attend a primary mass gathering site where the largest mass gathering of graduates in Australia occurs in a typical (non-pandemic) year; 325 indicated they would be celebrating at other locations (ie, secondary sites).Primary outcome measures Anticipated COVID-safe behaviour: physical distancing from friends and strangers and additional protective behaviours (hand hygiene and mask wearing).Results At all timepoints, participants anticipated maintaining appropriate (>1.5 m) physical distance from strangers, but not from friends (<0.5 m). Attendees at the primary site reported less physical distancing from friends over time throughout the mass gathering, χ2(4)=16.89, p=0.002. Physical distancing from strangers, χ2(4)=26.93, p<0.001, and additional protective behaviours, χ2(4)=221.23, p<0.001, also declined across the mass gathering among both groups. These reductions in COVID-safe behaviour were significant and enduring, with all declines persisting at follow-up.Conclusion It is critical that public health messaging and interventions emphasise the risks of disease transmission arising from other attendees who are known to us during mass gathering events, and that such messaging is sustained during and following the event to combat reductions in COVID-safe behaviour.